Pengaruh Investasi, Tenaga Kerja, Inflasi, san Konsumsi terhadap Pendapatan Domestik Regional Bruto - Jessica Ng; Angelina Angelina; Ketherine Alvia (Journal of Management and Bussines (JOMB), 2022)
This study aims to assess the Effect of Investment, Labor, Inflation, and Consumption on Gross Regional Domestic Income of North Sumatra for the 2017-2020 period. This research method is descriptive quantitative. The sample of this research is 120 data on the Gross Regional Domestic Income of North Sumatra for the 2017-2020 period. Method of data analysis using multiple linear regression test. The results showed, partially the results of the t test are as follows, a) the investment variable has a tcount value of -0.262, with a sig value of 0.794, and a -tcount > -ttable value, namely -0.262 > -1.980; b) the labor variable has a tcount value of 23.450, with a sig value of 0.000, and a tcount > ttable that is 23.450>1.980; c) the inflation variable has a tcount value of -0.092, with a sig value of 0.927, and a value of -tcount > -ttable that is -0.092>-1.980; d) the consumption variable has a tcount value of 5.122, with a sig value of 0.000, and a tcount > ttable that is 5.122>1.980. The results of the F test are the Fcount value of 230.202, with a sig value of 0.000, and Ftable (120-4-1=115) of 2.45. Partially, investment and inflation variables have no impact on GRDP in North Sumatra during the 2017-2020 period. Meanwhile, partially labor and consumption have an effect on GRDP in North Sumatra during the 2017-2020 period. Simultaneously, investment, labor, inflation, and consumption affect the GRDP in North Sumatra during the 2017-2020 period. Keywords: Inflation, Investment, Consumption, Gross Regional Domestic Product, Labor